2005
DOI: 10.1164/rccm.200409-1280oc
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Regenerates Alveoli and Vasculature in Elastase-induced Pulmonary Emphysema in Mice

Abstract: Adrenomedullin improved elastase-induced emphysema at least in part through mobilization of bone marrow cells and the direct protective effects on alveolar epithelial cells and endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 43 publications
(50 reference statements)
1
44
0
1
Order By: Relevance
“…Data for engraftment of marrow-derived cells as lung epithelial cells have been reported by our group as well as others (6)(7)(8)(9)(10)(11)(12)(13)(14), and some forms of lung injury promote mobilization of hematopoietic stem and progenitor cells from the BM into the circulation (14,15). There exists some controversy in this area, because a number of investigators using alternate approaches have found no evidence of BM contribution to epithelial repair in the murine lung (16)(17)(18).…”
Section: Bm Cells Can Develop Into Epithelial Cells In Micementioning
confidence: 76%
“…Data for engraftment of marrow-derived cells as lung epithelial cells have been reported by our group as well as others (6)(7)(8)(9)(10)(11)(12)(13)(14), and some forms of lung injury promote mobilization of hematopoietic stem and progenitor cells from the BM into the circulation (14,15). There exists some controversy in this area, because a number of investigators using alternate approaches have found no evidence of BM contribution to epithelial repair in the murine lung (16)(17)(18).…”
Section: Bm Cells Can Develop Into Epithelial Cells In Micementioning
confidence: 76%
“…Adm is an hypoxia-inducible peptide with vasodilative, antioxidative, and angiogenic properties and is highly expressed in the developing lung. Not only has Adm been reported to regulate cell growth and survival, to induce proliferation and migration of endothelial progenitor cells, to enhance the regenerating potential of the latter for pulmonary endothelium (36), and to regenerate alveoli and vasculature in elastase-induced pulmonary emphysema (35), but its role in alveolar development was recently shown (46). Lung expression of its transcript increases during alveolar development in rat lung also, and a requirement for Adm for alveolar septation and angiogenesis was demonstrated in this species (46).…”
Section: Discussionmentioning
confidence: 99%
“…47 Treatment with adrenomedullin was associated with increased numbers of mononuclear cells and sca-1 positive cells in circulating blood, and increased numbers of bone marrow derived cells within the elastasetreated lung. The authors concluded that adrenomedullin may improve emphysema by mobilizing bone marrow cells and protecting alveolar epithelia and endothelial cells against tissue destruction.…”
Section: Potential Mechanisms To Enhance Resident Stem Cell Regenerationmentioning
confidence: 92%